Next-generation sequencing reveals a case of Norrie disease in a child with bilateral ocular malformation - Li, Haijun; Li, Zhiming; Wang, Degang; Chen, Chuanming; Chen, Zhiqiang; Wang, Jinhua; Xu, Chenxia; Dong, Xingsheng (Frontiers in Genetics, 2022)
A Norrie disease protein gene (NDP) variant, c.174 + 1G> A, was found in a Chinese family through next-generation sequencing and verified with Sanger sequencing. A case of Norrie disease was reported in the first child, and their symptoms were consistent with the results of gene sequencing. The child’s mother, who was pregnant at the time, was found to be a carrier of the identified pathogenic variant. To determine if the fetus carried the same disease-causing variant, a prenatal examination and prenatal diagnosis was conducted. The fetus had bi-ocular vitreous abnormalities and complete retinal abnormalities. Genetic testing showed that the fetus had maternally inherited the NDP gene variant found in the proband. It was concurrently confirmed that the NDP gene variant led to the deletion of 246bp at the 3’ end of exon 2, resulting in the deletion of the Initiation codon and the occurrence of disease. Our study suggests that the diagnosis of rare diseases through next-generation sequencing, combined with prenatal ultrasound and prenatal diagnosis, can help families with known familial genetic diseases. Similarly, the findings of this study broaden the known genetic spectrum of Norrie disease.